Comparison of Air Contact And Distilled Water Distribution Method in The Conversion of Cao to Ca(OH)2 As A Precursor Hydroxyapatite Synthesis - Firnanelty Firnanelty; Andi Nur Fitriani Abubakar; Anas Qurniawan; M. A. Syam (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2023)
Eggshells containing CaCO3 have potential as bioceramics for several tissue engineering applications. The content of CaCO3 converted into Ca(OH)2 can be used as a precursor to implant material. The purpose of the study was to compare two methods of converting CaO into Ca(OH)2 as the primary material for making hydroxyapatite. The method used is direct contact with air and dissolution with water. Hydroxyapatite synthesis using Ca(OH)2 is calcined from CaCO3 with a sintering temperature of 900 °C. The result of calcination is in the form of CaO. The stages of obtaining Ca(OH)2 by converting CaO using two methods, namely direct contact with air and dissolution with water. The XRD characterization results obtained that Ca(OH)2 results from direct contact with air show the formation of phase (portlandite), which is characterized by its presence at the highest typical 2θ angles = 18.18°, 28.68°, 34.30°, 47.40°, 50.92°, 54.16°, and 62.62°. The XRD Ca(OH)2 pattern with the distilled water distribution process shows the formation of a phase (portlandite) characterized by its presence at angles of 2θ = 18.18°, 28.68°, 34.30°, 47.40°, 50.92°, 54.16°, and 62.62 °. The results of FTIR Ca(OH)2 characterization of air contact and water dissolution showed strong O-H functional groups at wave numbers 3643 cm-1 and 3642 cm-1, C-O groups at 1487 cm-1 and 1483 cm-1. This suggests that both methods can convert CaO to Ca(OH)2, which synthesizes hydroxyapatite. The hydroxyapatite characterization results obtained have met the standard.